Strahlresektion des Zeigefingers über den palmaren Zugang: operative Techniken - Rau, Johannes; Hug, Urs; Löw, Steffen; Unglaub, Frank; Müller, Lars Peter; Spies, Christian (Operative Orthopädie und Traumatologie, 2025)
Objective Improving the overall function of the hand by resection of the second ray applying the palmar approach in order to achieve an aesthetically pleasing postoperative result. Indications Mechanically disturbing proximal limb stump, high degree of instability of the index finger, chronic infection/osteomyelitis of the index finger, dystrophic index finger with impaired circulation, degloving injury, malformations, malignant tumours of the index finger, aesthetic improvement after index finger amputation. Contraindications Loss of grip strength that cannot be tolerated. Surgical technique Dissection of the index finger with resection of the second metacarpal at the proximal diametaphyseal region, mobilisation of the neurovascular bundles, and transposition of the first dorsal interosseus muscle onto the second dorsal interosseus muscle, reconstruction of the thumb-middle finger commissur. Postoperative management Sufficient dressing of the thumb-middle finger commissur with immobilisation for 2-5 days, then mobilisation for 8 weeks without forceful pinch grip between thumb tip und middle finger tip, mobilisation without limits after 3 months. Results After resection of the second ray, studies showed very pleasing aesthetic results with high patient satisfaction despite a decrease in grip strength.